2014
DOI: 10.1155/2014/963683
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Attitudes towards Proenvironmental Travel: An Empirical Study from Tangshan City in China

Abstract: Understanding people's attitudes towards proenvironmental travel will help to encourage people to adopt proenvironmental travel behavior. Revealed preference theory assumes that the consumption preference of consumers can be revealed by their consumption behavior. In order to investigate the influences on citizens' travel decision and analyze the difficulties of promoting proenvironmental travel behavior in medium-sized cities in China, based on revealed preference theory, this paper uses the RP survey method … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…According to the TPB, people act after they have formed a BI, which in turn is mainly predicted by attitude (ATT) towards a specific behavior; subjective norm (SN), which represents the expectations of other important people; and perceived behavioral control (PBC), which is the sense of being able to perform the desired action [ 15 , 18 ]. The TPB emphasizes psychological factors of related behaviors and is a universal model that could predict and explain various PEBs, such as pollution reduction intention [ 19 ], choice of travel mode [ 10 , 20 , 21 ], energy-saving behavior [ 22 , 23 , 24 ], use of alternative transportation [ 25 , 26 ], low carbon consumption [ 27 ] and so on. Many meta-analytic reviews have confirmed that individual BI and actual behavior can be well explained and predicted by the TPB [ 28 , 29 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…According to the TPB, people act after they have formed a BI, which in turn is mainly predicted by attitude (ATT) towards a specific behavior; subjective norm (SN), which represents the expectations of other important people; and perceived behavioral control (PBC), which is the sense of being able to perform the desired action [ 15 , 18 ]. The TPB emphasizes psychological factors of related behaviors and is a universal model that could predict and explain various PEBs, such as pollution reduction intention [ 19 ], choice of travel mode [ 10 , 20 , 21 ], energy-saving behavior [ 22 , 23 , 24 ], use of alternative transportation [ 25 , 26 ], low carbon consumption [ 27 ] and so on. Many meta-analytic reviews have confirmed that individual BI and actual behavior can be well explained and predicted by the TPB [ 28 , 29 ].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…In China, urban roads are becoming increasingly crowded, and the service quality of PT has seen a rapid downturn with the explosive growth of private cars. As a result, people have gradually abandoned PT, causing a vicious circle of urban traffic development [3]. Many governments have attempted to mitigate the trend of travelling by private cars through methods such as limiting travel and the purchase of cars, but to no avail.…”
Section: Introductionmentioning
confidence: 99%
“…These values match what would be expected from a sustainable transport system. Studies conducted in other geographical areas highlight that the gender variable is significant regarding attitudes and the propensity to want to change policies and behavior, but also that gender interacts and is co-dependent with other socio-demographic variables [66][67][68][69][70]. These studies on the gender differentials in behavior and attitudes suggest that, if women were equally represented in policymaking, the gender differentials would be carried over to impact policymaking.…”
Section: Literature Reviewmentioning
confidence: 96%